Development of X-ray mirrors manufacturing process with ELID-grinding and polishing methods. (1st October 2008) - Lin, Weimin; Morita, Shin-ya; Uehara, Yoshihiro; Ohmori, Hitoshi
A large ultraprecision aspheric grinding system with Electrolytic In-process Dressing (ELID) has been developed for the fabrication of large optical elements and components, which can be used in Synchrotron radiation facilities. An ELID-grinding unit is equipped on the machine, and long-term stabilised grinding performance was successfully achieved for SiC, Si, fused silica mirrors and many other hard material mirrors. This paper introduces the major specifications of the developed machine, and discusses certain representative applications in the R&D of special optical elements and components such as X-ray reflective optics, and use of a new feed method to improve the surface roughness of X-ray mirrors with ELID-grinding to obtain nanosurface. The polishing was implemented in two processes: preparing polishing and final polishing. In the final polishing process, the polyethyleneterephthalate fibres felt sheet was used and a very good surface roughness was obtained.